Developing human resources - Thomson, Rosemary (Butterworth-Heinemann OxfordGB, 1994)
Covers the skills and techniques required to design and implement an effective human resource development policy. Focuses on team building, recruitment and change management, as well as the role one plays in motivating and appraising his staff.